Resistance to benzimidazole anthelmintics in Philippine goats and sheep - Ancheta, P.B.; Dumilon, R.A.; Gray, G.D.; Villar, E.C.; Cerbito, W.A.; Ancheta, F.G. (Philippine Society of Animal Science, 2000)
There have been numerous Reports of resistance to anthelmintics in Southeast Asia, from Malaysia (Rahman, 1994), Thailand (Kochapakdee et al., 1995) and Indonesia (Dorny et al., 1995). In the Philippines, benzimidazole resistance in a field population of Haemonchus contortus from sheep has been described in Mindanao (Van Aken et al. 1994). Albendazole has been shown to be very poorly effective in Masbate province (as measured by change in prevalence) (Marbella, 1991). The study aims to investigate the extent of resistance to benzimidazole anthelmintics in Philippine goats and sheep, in regions with high densities of small ruminants population.